Prevalence of Migraine Headache in Epileptic Patients - Sayena Jabbehdari; Omid Hesami; Mehdi Chavoshnejad (Acta Medica Iranica, 2015)
Epilepsy is one of the most common neurological disorders which a physician might come across in his career life. On the other hand, migraine is common disorders in society chronic headache such as migraine in epileptic patients give ride to difficulties in seizure treatment due to altering the sleeping pattern and calmness disarrangement. Therefore, early diagnosis and suitable treatment in epileptic patients is definitely inevitable, and it will help in a more desirable patients' treatment. So we aimed to evaluate the prevalence of migraine in epileptic patients and relation between these two disorders. Number of 150 epileptic patients attended to neurology clinic of Shohadaye Tajrish Hospital and Iranian Epilepsy Association between June 2010 to May 2011 were fulfilled the questionnaire, and the data has been assessed by SPSS software. In this study, we used MS-Q (migraine screening -questionnaire) designed for early diagnosis of migraine in the general population. From all patients filling the questionnaire, the prevalence of migraine (with or without aura) was as follows: 23 persons had criteria compatible with migraine with aura; 26 patients had migraine without aura. Migraine was more common in these patients: persons with academic degrees, women, patients who were used 2 antiepileptic drugs, and patients with high BMI. In this study, we showed that migraine in epileptic patients is more prevalent than the general population. Thus, early diagnosis and efficient treatment of migraine headache in these patients is mandatory. More studies are needed for evaluation of this issue.